Aproveitamento do lodo de fossa séptica para produção de biodiesel, bio-óleo, gás, biocarvão e cinzas - Martins, Ana Vívian Parente Rocha (2017)
The increase in the generation of domestic sewage sludge in recent years due to investments in the sanitation sector has become a serious problem to be faced by sanitation professionals, and it is necessary to look for new routes of disposal and use for this waste. Thus, the objective of this research was to sewage sludge as an energy source for the production of biofuels and bio-adsorbents. A biodiesel production (esterification or transesterification) route was defined from the oil / grease characteristics of the scum and fat box and the in-situ transesterification process was used as a biodiesel production route from the sludge sludge. The process of continuous extraction and pyrolysis of sludge was used for the production of bio-oil, bio-coal, gases and ashes. The properties were investigated and potential applications were proposed. The biocarbons were characterized by the following techniques: total moisture, ash content, volatile materials, fixed carbon, higher calorific value, thermogravimetric analysis and specific surface area measurements and the ashes were characterized by x-ray fluorescence, x-ray diffraction , infrared spectrophotometry, specific surface area measurements, pH and zero load potential to be used for metal removal. All the extracted fatty materials presented high value of acidity index, indicative of characteristic of grease matter in advanced state of degradation, due to the environmental conditions, frying process of the oil and edible fat and the extraction process used. The in situ transesterification reaction eliminated the need to separate and extract the lipids and fatty acids contained in the sludge, since the lipid-containing fatty acids were simultaneously extracted and esterified. The biodiesel samples indicated significant amounts of methyl esters of capric acid (C10: 0), lauric acid (C12: 0), myristic acid (C14: 0), stearic acid (C18: 0), oleic acid (C18 : 1), linoleic acid (C18: 2) and eicosenoic acid (20: 1). The fatty acid methyl esters composing the septic tank sludge were found to be predominantly palmitic acid (C16: 0). The biodiesel composition of the sludge sludge had no significant difference in the biodiesel composition of vegetable oil. The thermogravimetric analysis under nitrogen flow showed that organic matter decomposition occurs between 200 and 500 ° C. The pyrolysis process had a yield of about 48, 30 and 22 mass% for the solid, liquid and gas phases, respectively. The biocarbons produced had carbon contents, volatile material and ashes of 6.2, 48 and 53.8% by mass, with a calorific value of 15.5 MJ kg-1, characteristics of amorphous carbon with no defined morphologies. Bio-oil and gas were tested on the lawn mower (2T). The tested products have started the engine, which confirms its properties as biofuels. Ash obtained from septic tank sludge showed good removal capacity for copper and lead ions in aqueous solutions. The equilibrium kinetics followed the pseudo-second order model. The Langmuir isotherm better adjusted to the experimental data in the systems studied and gave the best R2 for the copper ion. Therefore, sludge, by its abundance, is a material that can be easily reused as an energy source.